Neoacla (Hattersleya) chicaquensis sp. nov. (Orthoptera: Phalangopsidae), a new spider cricket from Andean cloud forests - García, Alexander García (Zootaxa, 2025)
Neoacla (Hattersleya) chicaquensis sp. nov., a new phalangopsid cricket species from the cloud forest of Chicaque Natural Park, is described. This species represents the first record of the genus Neoacla Desutter, 1988, in Colombia, the Andes, and the highland regions. Previously, all known species of this genus had only been recorded in forests ranging from Costa Rica to Ecuador and in the Amazon regions of Peru and Ecuador. Finally, the taxonomy, morphology, and distribution of the new species are discussed.